MODEL PENINGKATAN KOMITMEN SUMBER DAYA MANUSIA BERBASIS SPIRITUAL LEADERSHIP DAN SPIRITUAL SURVIVAL SERTA WORKPLACE SPIRITUALITY DENGAN MODERATING INDIVIDUAL SPIRITUALITY - Abdul Hakim; Azlimin - (Conference In Business, Accounting, And Management (CBAM), 2015)
This study purpose was to describe the influence of Spiritual Leadership and its influence and spiritual survival, on workplace spirituality as well as the commitment of human resources with moderation Individual spirituality inÂ  Sultan Agung Islamic Hospital . The population is all Sultan Agung Islamic Hospital employees totally 483 people . Samples were taken by purposive sampling approach to the criteria of the respondents who have worked over 2 years . The analysis tool is structural Equation Modeling ( SEM ) with Partial Least Square method ( PLS ) . The study results showed that spiritual leadership had no significant influenced on human resources commitment, but spiritual survival found the opposite. Spiritual leadership found significant influenced on workplace spirituality. Spiritual Survival could not be intervening variable but spirituality could. Interaction between individual spirituality and workplace spirituality could not moderated between workplace spirituality and human resources commitment. Â Keywords : Spiritual Leadership , Spiritual Survival , Workplace Spirituality , Individual Spirituality , Human Resources Commitment